Agriculture and Nutrition: Is the Marriage Working? - Ruel, Marie T. (2015)
"IFPRI at 40: Looking Back, Looking Forward" Special Event held on November 18, 2015. Presentation by Marie Ruel, Director of the Poverty, Health, and Nutrition Division (PHND) at IFPR.